Pulmonary hypertension and diastolic function of right heart chambers in adolescents with scoliosis - R. V. Enaldieva; A. G. Avtandilov; D. I. Nemanova (Российский кардиологический журнал, 2005)
Right heart chamber hemodynamics was assessed in adolescents with various stages of scoliosis. In participants with severe scoliosis, pulmonary hypertension was detected, with increased right ventricular volume and wall thickness, as well as myocardial dysfunction.